2014
DOI: 10.1093/cercor/bhu030
|View full text |Cite
|
Sign up to set email alerts
|

Sensorimotor Learning Enhances Expectations During Auditory Perception

Abstract: Sounds that have been produced with one's own motor system tend to be remembered better than sounds that have only been perceived, suggesting a role of motor information in memory for auditory stimuli. To address potential contributions of the motor network to the recognition of previously produced sounds, we used event-related potential, electric current density, and behavioral measures to investigate memory for produced and perceived melodies. Musicians performed or listened to novel melodies, and then heard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 111 publications
3
37
0
4
Order By: Relevance
“…However, the amplitude was larger for the action violation (i.e., when auditory feedback was lowered by the interval of one semitone for a single keystroke) compared to the perceptual violation (i.e., while listening to the same lowered interval), indicating that the expectations associated with the intention to produce a tone override those based on perceptual processes alone. This notion is corroborated by evidence showing that motor training of a specific melody enhances auditory expectancies by amplifying neural electrophysiological potentials arising from cortical motor structures (both premotor and supplementary motor regions) (Mathias et al, 2014). Furthermore, Ruiz et al (2011) explored EEG oscillatory markers predicting an error during musical performance.…”
Section: The Predictive Character Of Action-perception Couplingmentioning
confidence: 73%
“…However, the amplitude was larger for the action violation (i.e., when auditory feedback was lowered by the interval of one semitone for a single keystroke) compared to the perceptual violation (i.e., while listening to the same lowered interval), indicating that the expectations associated with the intention to produce a tone override those based on perceptual processes alone. This notion is corroborated by evidence showing that motor training of a specific melody enhances auditory expectancies by amplifying neural electrophysiological potentials arising from cortical motor structures (both premotor and supplementary motor regions) (Mathias et al, 2014). Furthermore, Ruiz et al (2011) explored EEG oscillatory markers predicting an error during musical performance.…”
Section: The Predictive Character Of Action-perception Couplingmentioning
confidence: 73%
“…Such a training-induced increase in the MMN to rhythmic or melodic deviation within a musical context points to an audio-motor coupling after sensorimotor training (Baumann et al, 2005; Bangert et al, 2006; Halwani et al, 2011; Jäncke, 2012; Mathias et al, 2015) leading to a better musical discrimination accuracy on the one hand and a better prediction ability about upcoming musical events on the other. It has been suggested that musical training establishes an internal forward model linking a musical tone with a specific motor movement resulting in strong associations between actions and their auditory consequences (Lee and Noppeney, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The difference in N2 amplitudes between the tapping positive and the listening positive conditions could be explained by 'the production effect' (MacLeod et al, 2010). For example, it has been shown that musical melodies played by the subject with normal auditory feedback are better recognized (which was associated with enhanced N2) compared to melodies that were only heard by the subject and not actively produced by them (Brown & Palmer, 2012;Mathias et al, 2015). Thus, this enhanced N2 will in turn lead to stronger memory retention.…”
Section: Discussionmentioning
confidence: 99%
“…With better memory representation of the stimuli, the memory violation had alerted the participants of the mismatch to a greater degree (associated with positive shifts), which was translated into the enhanced auditory N2 modulation. Indeed, Mathias et al (2015) reported the supplementary motor and premotor areas associated with auditory N2. Our finding of increased N2 in fronto-central areas in the tapping positive condition (see Figure 3, N2 topographic map for tapping positive condition) is consistent with the report of Mathias et al (2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation